Understanding the Use of Long-term Finance in Developing Economies - Martinez Peria, Maria (IMF Working Papers; Working Paper ;, 2017)
This short paper reviews recent literature on the use of long-term finance in developing economies (relative to advanced ones) to identify where long-term financing occurs, and what role different financial intermediaries and markets play in extending this type of financing. Although banks are the most important providers of credit, they do not seem to offer long-term financing. Capital markets have grown since the 1990s and can provide financing at fairly long terms. But few firms use these markets. Only some institutional investors provide funding at long-term maturities. Governments might help to expand long-term financing, although with limited policy tools.